The effect of use of egg citrate-yellow threatener with young coconut water level on quality Spermatozoa of the sheep - Hendriawan Kapoteng Bili; Agustinus Agung Dethan; Paulus Klau Tahuk (Journal of Tropical Animal Science and Technology, 2023)
This study aims to determine the effect of using young coconut water as a diluent on viability, spermatozoa abnormalities and pH of ram semen. This research has been carried out for 2 months, from June to August 2021, and has been carried out in a sheep semen shelter in Naiola Village, South Bikomi District, North Central Timor Regency and evaluated at the Laboratory of the Faculty of Agriculture, Timor University. This study used a completely randomized design (CRD) with four treatments and five replications. The R1 treatment without young coconut water, R2 treatment 10% young coconut water, R3 treatment 15% young coconut water, R4 treatment 20% young coconut water. The results showed that the effect of treatment was significantly different (P<0.05) on the viability of spermatozoa. The average spermatozoa viability of each treatment was P1 of 78,0±8,15, P2 of 75,2±7,79, P3 of 71,8±9,44 and P4 of 66,8±4,54. Spermatozoa abnormalities were not significantly different (P>0.05). Spermatozoa abnormalities of treatment P1 were 8,4±1,14, P2 was 9,2±0,83, P3 was 9,4±1,34 and P4 was 9,6±3,84. The degree of acidity (pH) of semen was significantly different (P<0.05) between treatments. The pH values ​​of each treatment were P1 of 6,79±0,16, P2 of 6,53±0,34, P3 of 6,47±0,33, and P4 of 6,35±0,20. So this study concluded that the addition of young coconut water level of (20%) can still maintain the viability, normality of spermatozoa and pH of ram semen.